Home » Past Questions » Mathematics » Find y, if \(\sqrt{12}-\sqrt{147}+y\sqrt{3} = 0\)

Find y, if \(\sqrt{12}-\sqrt{147}+y\sqrt{3} = 0\)


Question

Find y, if \(\sqrt{12}-\sqrt{147}+y\sqrt{3} = 0\)

Options

A) 5

B) 1

C) 7

D) 3

The correct answer is A.

Explanation:

\(\sqrt{12}-\sqrt{147}+y\sqrt{3} = 0\\\sqrt{4\times 3}-\sqrt{49\times 3}+y\sqrt{3} = 0\\2\sqrt{3}-7\sqrt{3}+y\sqrt{3} = 0\\y\sqrt{3} = 7\sqrt{3} - 2\sqrt{3}\\y=\frac{5\sqrt{3}}{\sqrt{3}}\\y = 5\)

More Past Questions:


Dicussion (1)

  • \(\sqrt{12}-\sqrt{147}+y\sqrt{3} = 0\\\sqrt{4\times 3}-\sqrt{49\times 3}+y\sqrt{3} = 0\\2\sqrt{3}-7\sqrt{3}+y\sqrt{3} = 0\\y\sqrt{3} = 7\sqrt{3} - 2\sqrt{3}\\y=\frac{5\sqrt{3}}{\sqrt{3}}\\y = 5\)

    Reply
    Like